Milieu therapy as a method for improving the quality of life of the old people - Oprya, Yevgen; Pustovoyt, Mykhailo (Psychosomatic Medicine and General Practice, 2021)
Relevance. Nowadays, both in developing countries and in industrialized countries, there is a process of increasing life expectancy, which together with the problem of low birth rates leads to the phenomenon of “aging population”. Providing care to the elderly is not only a purely medical problem, but the social aspect is equally important. An important component of the lifestyle of an elderly person is recreation - the processes of restoring vitality, relieving mental stress and recovery, carried out in various forms of recreation, nutrition, active or passive leisure. Modern society and the health care system face three most important tasks: continuing an active life with minimal losses from the disorders inherent in old age, combating high morbidity in old age and ensuring a dignified end to the lives of aging people. Although the provision of medical and social assistance to the elderly is organized and provided as needed, ensuring the accessibility and sufficient presence in their lives of the social aspect and its communicative component is not supported in our country at the state level and is not regulated by law. Purpose. The purpose of the work is to improve the quality of life of the elderly through the organization of the social component of life by arranging their leisure. Results. To achieve this goal, it was proposed to use the principles and methods of milieu therapy, which means “treatment by the environment”. Most often, milieu therapy refers to a form of psychotherapy that involves the use of therapeutic communities. Considering the goal, milieu herapy fully covers and meets the goals of rehabilitation of the elderly, and as a social technology allows to create an active living environment that encourages older people to “independent actions”, self-sufficiency, withdrawal from dependent moods and hyperprotection. Milieu therapy allows to activate the living environment of such people in accordance with their needs, interests, psychophysical condition, rehabilitation potential; and to optimize the work of staff in the direction of improving the efficiency of activities that will have a direct impact on quality of life. On the example of other countries, examples of the use of the principles of milieu therapy in the organization of daytime activities in the elderly are provided. Conclusions. Providing leisure for the elderly will be able to improve their quality of life, reduce the prevalence of somatic diseases and the risk of developing psychosomatic conditions in them, and thus reduce the burden on health care facilities. And the use of the principles of milieu therapy to solve problems will allow to organize it as effectively as possible.